New insights into the evolution of hybrid rifted margins: from crustal hyperextension to mantle exhumation at the Santos Basin (Brazil) - Stanton, Natasha; Gordon, Andres C. (Frontiers in Earth Science, 2025)
This study investigates the tectonic, magmatic and sedimentary architecture of the outer Santos Basin, using new ultra-deep high-resolution 3D seismic, gravimetric and magnetic data. We document a major crustal discontinuity that corresponds to a negative magnetic anomaly named Aquarius Lineament (AL). This is associated with N-S striking east-dipping detachment faults - the Aquarius Detachment System (ADS), that extends for more than 270 km. The ADS originated abrupt crustal necking, a core-complex and supradetachment basins. Its location and orientation coincide with major changes in continental lithosphere thickness, Moho depth, and stratigraphy. Seawards from the ADS the ductile lower crust disappears, and there is a transition to a hyperextended domain with deeply incising detachment faults reaching the mantle. The hyperextended domain lies adjacent to a thick magmatic crust that transitions into a domain where the Moho shallows reaching the base of the sediments. Altogether, these contrasting architectural elements reveal a complex lithosphere breakup during the Cretaceous that distinguishes the Santos Basin as a hybrid margin.